2012
DOI: 10.1590/s1806-83242012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic mapping of the hard palate and overlying mucosa

Abstract: The aim of this study was to measure the thickness of the hard palate and its overlying mucosa using cone-beam computed tomography (CBCT), for purposes of miniscrew placement. The sample comprised 36 CBCT scans of patients aged 12 to 52 years from a database of the Orthodontics Department of the Federal University of Rio de Janeiro. Paracoronal views of the palatal region were reconstructed at 4, 8, 16 and 24 mm posterior to the incisive foramen. In each reconstruction measurements were taken at the suture, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 19 publications
7
21
1
3
Order By: Relevance
“…In contrast, when Gracco et al, 11 used CBCT to analyse the PBT of 162 patients aged between 10 and 44 years and distributed into three groups (10-15 years, 15-20 years and >20 years), they found no significant differences in PBT between the groups. In agreement with those results and with the reports of other studies on the general population, 15,21,24 we observed no significant effect of age on PBT, either in individuals with DS or in controls. Justification of radiological examination must be particularly rigorous in children, as the radiation exposure dose in these patients is greater than in adults when the same exposure parameters are used.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In contrast, when Gracco et al, 11 used CBCT to analyse the PBT of 162 patients aged between 10 and 44 years and distributed into three groups (10-15 years, 15-20 years and >20 years), they found no significant differences in PBT between the groups. In agreement with those results and with the reports of other studies on the general population, 15,21,24 we observed no significant effect of age on PBT, either in individuals with DS or in controls. Justification of radiological examination must be particularly rigorous in children, as the radiation exposure dose in these patients is greater than in adults when the same exposure parameters are used.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, PBT usually decreased progressively in a lateral direction from the midline and also in an anteroposterior direction, with exception of the area of the median palatal suture; these findings confirm the results of previous series in the general population. 15,22,23 In the most anterior paracoronal sections from individuals with DS we detected an exception to this rule, as the PBT in the paramedian sections at 6 mm from the midline was greater than in the sections at 3 mm from the midline; we have not found any results in the literature with which to compare this finding. Nor have we been able to corroborate in other studies the morphometric differences in PBT observed between the DS group and controls in the area of the palatal suture and in the paramedian sections.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations